Post-Translational Modifications of STING: A Potential Therapeutic Target - Kang, Jiaqi; Wu, Jie; Liu, Qinjie; Wu, Xiuwen; Zhao, Yun; Ren, Jianan (Frontiers in Immunology, 2022)
Stimulator of interferon genes (STING) is an endoplasmic reticulum resident protein, playing essential roles in immune responses against microbial infections. However, over-activation of STING is accompanied with excessive inflammation and results in various diseases, including autoinflammatory and genetic diseases. Therefore, precise regulation of STING activities is critical for adequate immune protection while limiting abnormal tissue damage. Numbers of mechanisms regulate STING to maintain homeostasis, including protein-protein interaction and molecular modification. Among these, post-translational modifications (PTMs) are the key switch to accurately orchestrate the activation and degradation of STING by temporarily changing the structure of STING. In this review, we focus on the emerging roles of PTMs that regulate activation and suppression of STING, and providing forecasts about PTMs of STING in development of diseases and potential targeted therapy.